Technology of Ultrasonic Control Of Gas-Shielded Welding Process; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Solodsky S. A. Sergey Anatolievich (2016, 2016)
Title screen